Is Dhaka’s Weather More Conducive to Dengue Outbreaks? - Mahmud, Iffat; Raza, Wameq; Hossain, Rafi (World Bank, Washington, DC, 2021)
This report provides evidence from Dhaka to establish the linkage between climatic conditions and dengue outbreaks. In chapter two, the overall trend of dengue cases and associated deaths are presented; following which chapter three examines climate and dengue-related data for Dhaka to assess whether climatic conditions contributed to the major dengue outbreak in the capital city in 2019. Chapter four then presents the global evidence for the linkages between climate variability and the mosquito lifecycle. Analyses of weather variables for Dhaka between 1976 and 2019 are presented in chapter five to ascertain overall trends in climatic conditions. Chapter six provides a summary of key findings and recommends options for policymakers to consider.